(3eTGQb GdCfhGQ GdfHhjI ef UMGM GdCNHGQ GdeUWahjIs - (3GdUGZGfj, GdQVi, GdMSf Hf eMeO Hf GdMSf Hf MjOQ, (B650 (3g`s ((3jYbhH Hf EHQGgje Hf YHO GdcQjes)
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg eMjj GdQee bGd GdMSf Hf GdMSf GdUZGfj CeG HYO aEfj ef JOQLJ eQGbj GdTQa hJMQLJ ef eSGb GdSQa aeRLJ GdHMQjf jdJbjGf hZUJ Ydj ajgeG ef GdOQQ hGdYbjGf hSejJg eTGQb GdCfhGQ GdfHhjI ef UMGM GdCNHGQ GdeUWahjIs
(3BNQgG (B:s
(3cGf jgdd Hgf aj OHQ cd UdGI (B((3e(B) (3GHf YeQ (B: (3Gddge dHjc dHjc dG TQjc dHjc (B( (3cPG (B) (3Ef GdMeO hGdfYeI dc hGdedc dG TQjc dc cGf jdHj HgPg GdJdHjI aj MLg hYeQJg (B((3e(B) (3CfS (B: (3dHjc YeQI hMLGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 214s
(3eYLe GdeDdajf (B1 / 583s
(3cTa GdXfhf (B2 / 1688s
(3TPQGJ GdPgH (B5 / 250s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK hGdeUWdMs